The Readiness of Indonesian Youths Towards the Era of Digital Economy and Business - Amidjono, Dwi Sulistyorini; Husodo, Zaäfri A; Muchtar, Asiah (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2022)
The world is moving towards the digital economy and business era. Making Indonesia 4.0 was launched to prepare Indonesia ready to face the waves of change towards the Industrial 4.0 era and to be able to increase its competitiveness in the global arena. This study will share new insights into the level of readiness of the Indonesian youth to face the impact of digitalization. This study involved 8,347 youths aged 18-34 in Java who took online Financial Life Skills (FLS) training from June 2020 to April 2021. Cross-sectional data were collected through questionnaires and analyzed using an exploratory method. This study concluded that the readiness of Indonesian youth toward the digital economy and business era was still in the